Computational and Experimental Observation of Li‐Ion Concentration Distribution and Diffusion‐Induced Stress in Porous Battery Electrodes. Issue 9 (31st May 2017) - Ji, Liang; Guo, Zhansheng; Wu, Yajun
Abstract: A multiscale model of porous electrodes based on the Gibbs free energy is developed, in which the Li ion diffusion, diffusion‐induced stress (DIS), and polydispersities of electrode particle sizes are considered. The relationships between the size polydispersities and the concentration profiles and DIS evolution are investigated numerically. Li ion distributions are verified by in situ observation of color changes in a commercial porous graphite electrode. Simulations show small particles exhibit higher charge/discharge degrees and more rapid charge/discharge rates than large particles at the same macroscopic state of charge (SOC)/depth of discharge (DOD). Moreover, DIS is different in different size particles at a specific SOC and DOD, that is, there is a nonuniformly distributed stress field within porous electrodes during the charge/discharge processes. For SOC and DOD, which represent the macroscopic average states of charge and discharge, the influence of the microscopic SOC values and mass fractions of differently sized particles in porous electrodes should, therefore, be considered. Additionally, the fracture of particles in porous electrodes is likely caused by varied amplitude tensile‐compressive DISs during charge/discharge cycles. Reduced sizes and size polydispersities of electrode particles are prone to alleviate these stresses and thus improve battery performance. Abstract : Porous electrode : A model porous electrode is developed to determine the influence of size polydispersities on the Li‐ion concentration distribution and stress evolution. The simulated Li‐ion concentration distribution agrees well with the experimental results. The macroscopic state of charge/depth of discharge is related to the microscopic values and mass fractions of differently sized particles. Furthermore, the electrode is fractured by the various amplitude tensile‐compressive diffusion‐induced stresses during charge/discharge cycles.